Repositórios Digitais: identificando fatores de sucesso para as Bibliotecas Digitais e Repositórios Institucionais - Nascimento, Aline Vieira do (2014)
The work has as its central focus digital repositories among them the digital libraries and institutional repositories, mechanisms used to facilitate open access to scientific information – movements incited by scientific communities existing in universities and research institutes to disseminate the results of research. It approaches the importance of production and communication in shared science in books and scientific journals. It reveals the course of digital libraries and institutional repositories, concepts, goals and functions which enable the interoperability of systems propitiating the sharing of information between the scientific communities and society in general through the open access. It identifies the elements of success in repositories through systematic literature review distributed into seven distinct stages resulting in three analyzed articles. Then the challenges, actions and opportunities for practice of each element detected in the analyzed articles were punctuated. The result of the analyses pointed to a set of actions that must be observed for developers of digital repositories, including design, implementation and management.